2009
DOI: 10.1016/j.jsat.2008.04.001
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative review of the ubiquitous relapse curve

Abstract: The primary goal of this study is to ascertain whether relapse to drug dependence, in terms of continuous abstinence assessment, exhibits a typical pattern that can be characterized by a common quantitative function. If the relapse curve is indeed ubiquitous, then some underlying mechanism must be operating to shape the curve that transcends variables such as drug class, population or treatment type. Survival analyses are performed on 20 alcohol and tobaccotreatment studies using the proportions of individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
63
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 35 publications
(12 reference statements)
8
63
0
1
Order By: Relevance
“…Across all three drugs, most patients relapsed early post-treatment, and thereafter, relapse rates decelerated dramatically. In a recent quantitative review of treatment outcome studies on nicotine and alcohol, Kirshenbaum, Olsen, and Bickel (2009) demonstrated that the basic shape of the relapse curve tends to be uniform-'the rate of relapse decelerates after initial abstinence has been achieved, and therefore, the amount of accumulated time abstinent may be the transcending variable that operates to shape the relapse curve' (p. 8). In short 'abstinence begets abstinence' (p. 9).…”
Section: Temporal Course Of Relapse Patternsmentioning
confidence: 99%
“…Across all three drugs, most patients relapsed early post-treatment, and thereafter, relapse rates decelerated dramatically. In a recent quantitative review of treatment outcome studies on nicotine and alcohol, Kirshenbaum, Olsen, and Bickel (2009) demonstrated that the basic shape of the relapse curve tends to be uniform-'the rate of relapse decelerates after initial abstinence has been achieved, and therefore, the amount of accumulated time abstinent may be the transcending variable that operates to shape the relapse curve' (p. 8). In short 'abstinence begets abstinence' (p. 9).…”
Section: Temporal Course Of Relapse Patternsmentioning
confidence: 99%
“…Irrespective of the type of intervention employed, at least 60% of those treated for an AUD will relapse to a period of hazardous alcohol consumption, typically within 6 months of treatment (Meyerhoff and Durazzo, 2010, Witkiewitz, 2011, Kirshenbaum et al, 2009). Resumption of hazardous alcohol consumption levels within 6 months of treatment is associated with extended periods of relapse and clinically significant impairments of psychosocial functioning (e.g., unemployment, relationship/marital discord, legal entanglements) over the ensuing 1–3 years (Durazzo et al, 2008, Maisto et al, 2006, Maisto et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Without specific treatment, approximately 80-90 percent of all patients who underwent detoxification treatment will relapse within the next 6 months (Boothby & Doering 2005). Interestingly, the majority of relapses (approximately 60-70 percent) appear within the first 3 months after detoxification (Kirshenbaum et al 2009). …”
Section: Introductionmentioning
confidence: 99%